Integration of Medical Roles and Islamic Spirituality in the Health of Students at Islamic Boarding Schools - Nur Azizah A.S; Dewi Masithah; Rahmadinah Diva Zhavira; Rizqi Mahmud Idris; Khadijah Khairul Bariyah (UKInstitute, 2026)
The mental health of students in Islamic boarding schools is often neglected due to stigma, low literacy, and misunderstandings linking it to supernatural factors such as possession. This condition makes students reluctant to seek medical help and prefer a purely spiritual approach. This community service program aims to improve mental health literacy by integrating medical approaches and Islamic spirituality, which students and caregivers find more easily acceptable. The activity was carried out at Hidayatullah Al-Muhajirin Bangkalan Islamic Boarding Schools involved 30 students in counseling sessions, 48 students, and 15 caregivers in free health check-ups. The activity methods included an initial survey, interactive counseling, discussions, pre- and post-test questionnaires, and basic health services. Results showed an average increase in students' knowledge scores of 13 points after the counseling, indicating the program's effectiveness in improving mental health awareness. This increased insight also encouraged students to discuss psychological issues without stigma. The material was delivered by integrating Islamic values such as dhikr (remembrance of God), prayer, and meditation (contemplation). The free health check-ups also emphasized the importance of physical and mental balance from an Islamic perspective. This activity has implications for ongoing educational forums, caregiver training in early detection of mental disorders, and the development of medical-spiritual-based counseling services. This program has proven effective as an intervention model that can be replicated in other Islamic boarding schools, while also strengthening community involvement in creating a more caring and supportive environment for students' mental health.